Study on the terahertz domain dielectric relaxation response and mechanism of thermal‐oxidative aged cross‐linked polyethylene - Mengqi Wang; Shihang Wang; Xinyu Li; Yang Feng; Jingran Wang; Shengtao Li (High Voltage)
Abstract To further study the thermal‐oxidative ageing mechanism of crosslinked polyethylene (XLPE), the terahertz frequency domain dielectric parameters and relaxation phenomena of thermal‐oxidative aged XLPE are analysed using terahertz time domain spectroscopy. It is found that the real part of the terahertz dielectric constant increases with the increase of thermal‐oxidative ageing duration, and the imaginary part shows an overall upward trend. Relaxation of the complex dielectric constant of the aged XLPE samples is obvious. Through the second‐order Cole–Cole equation fitting, it is found that there are two relaxation processes around 0.15 and 1.5 THz, and the relaxation strength gradually increases with the ageing time. To explain this phenomena, microstructure changes and crystallisation behaviours are characterised using Fourier transform infrared spectrum and differential scanning calorimetry, respectively. It is suggested that the two relaxations may be caused by elastic dipole polarisation originating from the angular deflection of polar groups and stretching rotation of hydrogen bond. In addition, by comparing the relaxation strength in different temperatures, the source of the relaxation process is further confirmed.